TRPC1 Inhibits Cell Proliferation/Invasion and Is Predictive of a Better Prognosis of Esophageal Squamous Cell Carcinoma - Zeng, Yun-Zhu; Zhang, Yong-Qu; Chen, Jiong-Yu; Zhang, Li-Ying; Gao, Wen-Liang; Lin, Xue-Qiong; Huang, Shao-Min; Zhang, Fan; Wei, Xiao-Long (Frontiers in Oncology, 2021)
Background and objectives: Esophageal squamous cell carcinoma (ESCC) is a frequently malignant tumor with poor prognosis despite the development of comprehensive therapeutic strategies, for which there is still a lack of effective prognostic factors. Previous studies found that the abnormal expression of TRPC1 is closely related to the proliferation, invasion, metastasis, and differentiation of various tumors. However, the relationship between TRPC1 and ESCC is currently unclear. The present study aimed to clarify the clinical significance of TRPC1 and to preliminarily assess the molecular mechanism by which TRPC1 regulates cell proliferation, migration, and invasion in ESCC. Materials and methods: Immunohistochemistry (IHC) was used to determine the expression of TRPC1 and Ki-67 in 165 cases of ESCC. The correlations between TRPC1 expression and clinicopathological characteristics were determined, and both univariate and multivariate analyses were utilized to quantify the impact of TRPC1 expression on patient survival. Cell Counting Kit-8, scratch wound healing, and transwell assays were used to determine the effects of TRPC1 on proliferation, migration, and invasion in ESCC, respectively. Results: The expression level and area with positivity for TRPC1 were decreased in ESCC, and higher TRPC1 was associated with low lymph node metastasis (P<0.001), high differentiation (rs= 0.232, P=0.003), and low Ki-67 (rs = -0.492, P<0.001). We further revealed that low expression of TRPC1 was associated with poor prognosis (Disease-free survival, DFS, P=0.001; Overall survival, OS: , P=0.004). Furthermore, we showed that downregulation of TRPC1 promoted the proliferation, migration, and invasion in vitro. In contrast, overexpression of TRPC1 inhibited the proliferation, migration, and invasion of KYSE150 cells (P<0.01), in a manner at least in part mediated through the AKT/p27 pathway. Conclusion: In ESCC, the expression level of TRPC1 was decreased and higher TRPC1 was associated with low lymph node metastasis, high differentiation, and low Ki-67. TRPC1 inhibited the proliferation, migration, and invasion of EC9706 and KYSE150 cells, at least, in part mediated through the AKT/p27 pathway in vitro. The downregulation of TRPC1 may be one of the most important molecular events in the malignant progression of ESCC. TRPC1 could be a new candidate prognostic factor of ESCC.